CALCULATION OF SHRINKAGE BY COMPARING BETWEEN THE CALCULATIONS OF PT. PLN ULP LHOKSEUMAWE CITY WITH ETAP SOFTWARE CALCULATION AFTER CHANGES IN OPERATING PATTERNS IN 2023 - Hasibuan, Arnawan; Afrizal, Ari; Fariadi, Dedi; Taufiq; Nisa, Fidyatun (TESLA: Jurnal Teknik Elektro, 2024)
In order to provide electrical energy, the distribution network has a crucial role in delivering power from the plant to the end customer. However, the phenomenon of technical shrinkage during the dispensing process can have a significant impact on the efficiency and reliability of the system as a whole. This study aims to compare the results of calculating technical shrinkage in electrical energy distribution networks, especially in the electric power system of Lhokseumawe city. Calculation of shrinkage carried out by PT. PLN ULP Lhokseumawe Kota presents a value of 13,955,404 kW or 72% of the total power, with an average monthly shrinkage of 1,549,434 kW. There is a difference between the calculations of PT. PLN ULP Lhokseumawe Kota with the help of ETAP software, where the value of the shrinkage difference is 76.7 kW. These differences can be due to different calculation methods, different operating patterns of electrical systems, and the possibility of adding new users. In addition, the use of the latest equipment and the introduction of new data can also affect the difference in calculation results. Abstrak Dalam rangka penyediaan energi listrik, jaringan distribusi memiliki peran krusial dalam mengantarkan daya dari pembangkit ke pelanggan akhir. Namun, fenomena susut teknis selama proses penyaluran dapat berdampak signifikan pada efisiensi dan keandalan sistem secara keseluruhan. Penelitian ini bertujuan untuk membandingkan hasil menghitung susut teknis dalam jaringan distribusi energi listrik, khususnya di sistem tenaga listrik kota Lhokseumawe. Perhitungan susut yang dilakukan oleh PT. PLN ULP Lhokseumawe Kota menyajikan nilai sebesar 13.955.404 kW atau 72% dari total daya, dengan rata-rata susut bulanan mencapai 1.549.434 kW. Terdapat perbedaan antara perhitungan PT. PLN ULP Lhokseumawe Kota dengan bantuan software ETAP, dimana nilai selisih susut adalah sebesar 76,7 kW. Perbedaan ini dapat disebabkan oleh metode perhitungan yang berbeda, pola operasi sistem kelistrikan yang berlainan, dan kemungkinan penambahan pengguna baru. Selain itu, penggunaan peralatan terbaru dan pengenalan data baru juga dapat memengaruhi perbedaan hasil perhitungan